Bio-based coatings for reducing water sorption in natural fibre reinforced composites. Issue 1 (December 2017) - Mokhothu, T.; John, M.
Abstract In this study, bio-based coatings were used for reducing water sorption of composites containing flame retardant treated natural fibres and phenolic resin. Two types of coatings; polyfurfuryl alcohol resin (PFA) and polyurethane (PU) were used on the composites and compared with a water resistant market product. Uncoated and coated samples were conditioned at 90 °C and relative humidity of 90% for three days and the relative moisture content and mechanical properties after conditioning were analysed. In addition, the changes in the weight loss of the conditioned samples were also investigated by thermogravimetric analysis. The moisture diffusion characteristics of coated laminates were also studied at room temperature under water immersion conditions. PFA coated samples showed better moisture resistance and mechanical performance than other bio-based coatings when subjected to long term environmental aging.